Molecularly Imprinted SERS Plasmonic Sensor for the Detection of Malachite Green - Hao Zhang; Dani Sun; Yuhao Wen; Mengyuan Wang; Jingying Huang; Ziru Lian; Jinhua Li (Biosensors)
Malachite green (MG) is a highly toxic dye commonly used in industries and aquaculture, leading to significant environmental contamination and health hazards. Therefore, sensitive and selective detection of MG in real samples is urgently needed. This study presents the development of a molecularly imprinted surface-enhanced Raman spectroscopy (MI-SERS) plasmonic sensor for the rapid and sensitive detection of MG. The sensor consists of a gold nanostar (Au NS) layer as the SERS substrate and an imprinted polydopamine layer containing specific recognition sites for MG. Taking full advantage of the plasmonic effect of SERS and selective recognition capability of imprinted materials, under optimized conditions, the sensor demonstrated high sensitivity, with a detection limit of 3.5 × 10−3 mg/L, excellent selectivity against interference from other organic dyes, and robust performance with recoveries of 90.2–114.2% in real seawater samples. The MI-SERS sensor also exhibited good reproducibility, stability, and reusability. These findings suggest that the MI-SERS sensor is a promising tool for real-time monitoring of MG contamination in complicated samples.